'Envilution™' chamber for performance evaluation of low-cost sensors. (15th February 2020) - Omidvarborna, Hamid; Kumar, Prashant; Tiwari, Arvind
Abstract: The emergence of low-cost sensors (LCSs) has rapidly changed the landscape of air pollution monitoring. Unlike regulatory standards with comprehensive processes for performance evaluation and certification for reference equipment, no accreditations or regulatory standards exist for LCSs. Hence, calibration and performance assessment of the LCSs are carried out via co-location experiments with reference instruments under limited ranges of environmental conditions and pollutant concentrations. We designed and tested an environmental-pollution (referred to as 'Envilution™') chamber to generate controlled environment for temperature and relative humidity (RH) along with different concentrations of particles so that varied real-world environmental conditions and pollution concentrations can be generated for the performance evaluation of LCSs. The custom-made 125L Envilution™ chamber consists of a humidifier/dehumidifier system, heat pump, particulate matter (PM) generator, a connection for gaseous air pollutants and reference measuring instruments. In the experiments under controlled conditions, the chamber was able to maintain diverse ambient and indoor environmental conditions (temperature range from 5 to 40 °C and RH from 10 to 90%) and stable pollutant concentrations, thereby enabling the use of chamber as a reference environment for LCSs' testing. For demonstration, the assessment was conducted based on temperature/RH (HDC1000 digital) and PM2.5 (HPMA115S0 Honeywell) sensors. A Vaisala HMT120 temperature/RH sensor and optical particle counter (Grimm EDM 107) were employed as reference instruments. The evaluation of LCSs, which were placed inside small enclosure kits, showed excellent correlation for temperature (R 2 > 0.96), RH (R 2 = 0.99), and PM2.5 (R 2 = 0.97) with the reference instruments. The LCSs also demonstrated high linearity agreement (R 2 > 0.98) among themselves at temperature (5–35 °C), RH (20–80%), PM2.5 (65–200 μg/m 3 ) measurement ranges. The unique features of the chamber, including affordable cost, small size and lightweight, low maintenance/operational costs and ease of operation, has the potential to make it an on-demand package for LCSs' testing. Graphical abstract: Image 1 Highlights: Envilution™ chamber is required due to an increase in air sensor kits' users. A 125 L Envilution™ chamber with an affordable cost was developed for LCS testing. The chamber can generate a wide range of atmospheric environmental conditions. The various PM and gaseous pollutants in different concentrations can be simulated. Small size and light-weight, low maintenance/operational costs and ease of operation.